A Genetic Algorithm Based Elevator Dispatching Method For Waiting Time Optimization. Issue 3 (2016) - Tartan, Emre Oner; Ciftlikli, Cebrail
Abstract: Elevator group control is one of the important issues in vertical transportation systems in buildings. For an efficient group control algorithm it is required to overcome some optimization problems. From the perspective of quality of service two fundamental parameters needed to be optimized are waiting time and journey time. Elevator group control algorithms can be developed based on soft computing methods used for optimization. In the last decade Genetic Algorithm(GA) has attracted researchers' attention as the suitability for the encoding car dispatching problem. In this study we enhance a previous study suggested for optimization of waiting time. The proposed method reduces average waiting time and uses a simpler encoding approach which results in efficiency in terms of computational cost. We explicitly demonstrate the method on the referred scenario for the purpose of visualization and insight.